Congenital Myasthenic Syndrome in a Mixed Breed Dog - Blakey, Theresa J.; Michaels, Jennifer R.; Guo, Ling T.; Hodshon, Amy J.; Shelton, G. Diane (Frontiers in Veterinary Science, 2017)
A 6-month-old, male, intact mixed breed dog was presented for a 3-month history of progressive generalized weakness. Neurologic examination revealed non-ambulatory tetraparesis, weakness of the head and neck, and decreased withdrawal reflexes in all limbs consistent with a generalized neuromuscular disorder. Electromyography and motor nerve conduction velocity were normal. Repetitive nerve stimulation showed a decremental response of the compound muscle action potential with improvement upon intravenous administration of edrophonium chloride. The serum acetylcholine receptor antibody titer was within reference range. Cerebrospinal fluid analysis was unremarkable. A presumptive diagnosis of post-synaptic congenital myasthenic syndrome was made. Treatment with pyridostigmine bromide was initiated with titrated increases in dosage resulting in an incomplete improvement in clinical signs. The dog was euthanized 2 months after initiation of treatment due to poor quality of life. Immunostaining for localization of antibodies again end-plate proteins in muscle biopsies was negative. Immunofluorescence staining for acetylcholine receptors in external intercostal muscle biopsies showed absence of acetylcholine receptors and biochemical quantitation showed a markedly decreased concentration of acetylcholine receptors with no detectable acetylcholine receptor-bound autoantibody which confirmed the diagnosis of a congenital myasthenic syndrome. Evaluation for the CHRNE mutation previously identified as the causative mutation of congenital myasthenic syndrome in Jack Russell Terriers was performed and was negative. This is the first reported confirmed case of congenital myasthenic syndrome in a mixed breed dog and provides a review of typical clinical and diagnostic findings as well as treatment considerations.